Progress Report on the Project "Purpose and Promise: A History of the Evolution of Higher Education in The Bahamas: with particular reference to the History of The College of The Bahamas" August 1, 2009 – April 30, 2010 - Bethel, Keva Marie (International Journal of Bahamian Studies, 2016)
On June 30, 2009, I signed an Agreement with The College of The Bahamas to undertake a Project aimed at conducting research and writing on the history of post-secondary education in The Bahamas, with particular reference to the history of the College of The Bahamas. In order to facilitate this undertaking, The College appointed me as Scholar-in-Residence from August 1, 2009 to September 30, 2011, on the understanding that I would undertake research and write a book on the subject described.The report that follows documents the activities that I have undertaken to date in fulfilling my commitments in relation to this project and a sample of preliminary findings emerging from the research so far conducted.--Dr Bethel died in February 2011 before completing the book. This article is an outline of the work she completed. A commentary on the outline is included in this volume of the journal: see Davis. L. A. (2016). Commentary on K. M. Bethel, Progress Report on the Project. The International Journal of Bahamian Studies, 22, 74-82. http://dx.doi.org/10.15362/ijbs.v22i0.275